PERBEDAAN HASIL BELAJAR AKUNTANSI MENGGUNAKAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE TEAMS GAME TOURNAMENT BERBANTU MEDIA MONOPOLI DAN TIPE TALKING STICK PADA SISWA SMK NEGERI 1 TEBING TINGGI KABUPATEN KEPULAUAN MERANTI - Nada Kasih Ijora; Sumarno Sumarno; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine differences in accounting learning outcomes using cooperative learning model by the type of teams game and tournament which assisted by monopoly media and Talking Stick type. This is an experimental research. The population of this research was all 10th grade students of accounting of SMKN 1 Tebing Tinggi Meranti Islands Regency. The 10th grade of accounting 1 and accounting 3 were chosen as the sample in this research. The data of this research were gained by observation and test technique. The hypothesis was tested by using t-test formula. Based on the calculation of the different test, it can be seen that the accounting learning results using the TGT learning model assisted by monopoly media with an average value of 83.13 is greater than the accounting learning results using the model talking stick while for classes using the Talking Stick learning model with an average value of 76.83, the difference is close to significant. Based on the results of the n-gain test, the TGT learning model assisted by monopoly media showed a value of 0.57 while the Talking Stick learning model was worth 0.14. It was concluded that the cooperative TGT learning model assisted by monopoly media had a higher influence on accounting learning outcomes than the Talking Stick learning model.Key Words: TGT, Talking Stick, Learning Achievement